One Year Facing COVID. Systematic Evaluation of Risk Factors Associated With Mental Distress Among Hospital Workers in Italy - Bonzini, Matteo; Comotti, Anna; Fattori, Alice; Cantù, Filippo; Colombo, Elisa; Tombola, Valentina; Myslymi, Eralda; Gatti, Michele; Stucchi, Giulia; Nava, Carlo; Bordini, Lorenzo; Riboldi, Luciano; et al. (Frontiers in Psychiatry, 2022)
Introduction: Italy was the first Western country affected by the Covid-19 pandemic that still constitutes a severe challenge for healthcare workers (HCW), with a deep impact on their mental health. Several studies confirmed that a considerable proportion of HCW developed adverse psychological outcomes. To focus on preventive and rehabilitation measures it is fundamental to identify risk factors of psychological impairment (PsI). We systematically examined the psychological well-being of all employees in a large University Hospital in Italy, using validated psychometric scales in the context of Occupational Health surveillance. Methods: In the period July 2020-July 2021 we enrolled 990 workers. For each subject, the psychological well-being was screened in two steps. The 1st level questionnaire collected gender, age, occupational role, personal and occupational Covid-19 exposure, general psychological discomfort (GHQ-12), post-traumatic stress symptoms (IES-R), and anxiety (GAD-7). Workers showing PsI (i.e. test scores above the cut-off in at least one among GHQ-12, IES-R, and GAD-7) have been further investigated by the 2nd level questionnaire (psycho-diagnostic) composed by PHQ-9, DES-II, and SCL-90 scales. If the 2nd level showed clinically relevant symptoms, we offered individual specialist treatment (3rd level). Results: 316 workers (32%) presented signs of PsI at the 1st screening questionnaire. Women, nurses, subjects engaged in the Covid-19 area and with an infected family member showed significantly higher PsI risk. PsI prevalence was strongly associated with the pandemic trend in the region but sensibly decreased after January 2021, when almost all workers received the vaccination. Only a proportion of subjects with PsI presented clinically relevant symptoms (2nd level screening) on PHQ-9 (35%), DES (20%), SCL-90 (28%). These symptoms were not associated to direct working experience with Covid-19 patients nor with Covid-19 experience in the family and seemed not to be influenced by the pandemic waves or workers vaccination. Conclusions: The evaluation of psychological wellbeing of all hospital workers, directly or indirectly exposed to pandemic consequences, constitutes a unique condition to detect individual, occupational, and non-occupational risk factors for psychological impairment in situations of high stress and/or disasters, as well as variables associated with symptoms chronicization.